2014
DOI: 10.3892/or.2014.2989
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-26a is associated with metastatic potential and the poor prognosis of osteosarcoma patients

Abstract: Abstract. Accumulating evidence indicates that microRNAs are involved in multiple processes in cancer development and progression. microRNA-26a (miR-26a) has been identified as a tumor suppressor and its downregulation is associated with poor prognosis in several types of human cancer. However, the specific function of miR-26a in osteosarcoma remains unclear.In the present study, we found that the expression of miR-26a in osteosarcoma tissues and cell lines was much lower than that in the normal controls, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 32 publications
3
33
0
1
Order By: Relevance
“…Interestingly, the top three most significantly enriched upstream regulators were microRNAs (miRNAs) implicated in human osteosarcoma, namely the genes encoding miR-181 ( P = 2.18 × 10 −5 ), miR-17-5p ( P = 3.42 × 10 −5 ) and miR-26a-5p ( P = 3.06 × 10 −7 ) ( Fig. 3b and Supplementary Table 4 ) 4042 . The remaining top regulators were MAPK7 ( P = 7.64 × 10 −5 ) and WT1 ( P = 8.50 × 10 −5 ), both implicated in osteosarcoma as prognostic markers of poor outcome 43,44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the top three most significantly enriched upstream regulators were microRNAs (miRNAs) implicated in human osteosarcoma, namely the genes encoding miR-181 ( P = 2.18 × 10 −5 ), miR-17-5p ( P = 3.42 × 10 −5 ) and miR-26a-5p ( P = 3.06 × 10 −7 ) ( Fig. 3b and Supplementary Table 4 ) 4042 . The remaining top regulators were MAPK7 ( P = 7.64 × 10 −5 ) and WT1 ( P = 8.50 × 10 −5 ), both implicated in osteosarcoma as prognostic markers of poor outcome 43,44 .…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the majority of SB-mutagenized tumors had loss of Trp53 function and the loss of TP53 in many human osteosarcomas strongly suggest that loss of both these genes is a cooperative event driving osteosarcomagenesis 14 . Additionally, copy number loss of PTEN has been observed in >60% of human osteosarcomas, and oncogenic miRNAs implicated in osteosarcoma target PTEN 4042,46 . To validate this cooperation in osteosarcoma and generate a new model genetically relevant to human disease, we combined conditional Pten (loxP-flanked exons 4 and 5) and Trp53 R270H alleles with Sp7-cre mice (Trp53-Pten mice) 40,46,47 .…”
Section: Resultsmentioning
confidence: 99%
“…The error bars represent the standard error. ⁄ p < 0.05, ⁄⁄ p < 0.01. prognosis in osteosarcoma patients [23]. miRNA-26a expression levels are lower in human nasopharyngeal carcinoma (NPC) specimens, and its overexpression significantly reduces cell-cycle related enhancer of EZH2 and Cyclin D2 [16].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Studies have reported that several miRNAs were dysregulated in osteosarcoma tissues or cell lines, including miR-17, miR-26a, miR-126, and miR-145. [7][8][9] MicroRNAs also play a role in chemoresistance of osteosarcoma. Recent studies found that miR-33a is upregulated in chemoresistant osteosarcoma and could promote osteosarcoma cell resistance to cisplatin via downregulating twist.…”
Section: Introductionmentioning
confidence: 99%